The Visual Frontiers of the Linguistic Turn: Effects of Presence and Effects of Meaning in Historical Cinema: Crossed Reflections on the Work of Robert A. Rosenstone and H.U. Gumbrecht - de Miguel, Aitor Bolaños (História da Historiografia: International Journal of Theory and History of Historiography, 2025)
Historical cinema is one of the most important audiovisual media through which we represent the past. Cinema challenges our conception of the past and history, as it adds to the usual interpretive activity (understood as the central practice of the humanities and social sciences) the presence, real or fictionalized, of the past. Following Gumbrecht, historical cinema expands the boundaries of our purely textual conception of history, highlighting the effects of meaning but also the effects of presence of the visualized past. Its nature is to force and expand the limits of a historiographical conception inspired first by historicism and then by the linguistic turn. It is not only a matter of interpreting the past but also of visualizing it, feeling it, and being moved by it. According to Rosenstone, historical cinema can provide a realistic and authentic depiction of past events, while also powerfully redefining them for current generations. And this is the visual challenge of historical cinema, especially experimental cinema, which complements the critical reflection that the linguistic shift has brought to the discipline of historiography. Gumbrecht's historical theory connects with Rosenstone's defense of historical cinema.